Dalit diary, 1999-2003 : reflections on apartheid in India : selected from the weekly column in the Pioneer - Prasad, Chandra Bhan (Navayana, 2004)
On political activity and social conditions of Dalits in India; articles serialized previously in Indian daily, The Pioneer.